Reformulation of Regional Autonomy Strategy for Tourism Development in Indonesia - Widodo, Sugeng (International Journal of Economics, Business and Management Studies, 2019)
Regional autonomy is not something new in governance in Indonesia. Efforts are being made to increase the potential of various sectors and industry resources to achieve the goal of community welfare has been widely scheduled for the past two decades. However, the realization is not yet optimal. One of the leading sectors of the government today is the development of tourism. Regional autonomy has a basic role in empowering the tourism sector. Various problems regarding performance issues in the tourism sector so far have become quite comprehensive challenges and obstacles. As a potential tourist destination, reformulation of the right strategy is certainly needed. By using analysis of literature studies and based on a review of previous research to strengthen the strategy reformulation needed. The researcher concludes that tourism development in Indonesia can be done with nine reformulation strategies that are accelerative and effective, namely: cultural autonomy, developing rural tourism, building competitiveness, special autonomy, accural basis implementation, empowering community leaders, capital allocation and sustainable development.